Examining Consonant Fossilization in EFL Teachers’ Pronunciation: Insights from a Case Study of a Private High School in Yogyakarta - Alya Savira; Surono Surono; Azwar Abbas (Universitas Pendidikan Mandalika, 2026)
Although fossilization is a well-studied aspect of interlanguage among learners and teachers, consonant fossilization in the context of EFL teachers’ classroom practices remains under-explored. Since, Existing literature has primarily focused on EFL students, while EFL teachers are often assumed to possess near-native pronunciation. Within in SLA, consonant fossilization is significant because the stabilization of non-target phonological patterns can shape learners’ interlanguage development. Moreover, in EFL contexts, where the EFL teachers serve as primary pronunciation models, fossilized consonant errors may affect comprehensibility and the quality of classroom input. This study drew on interlanguage theory, fossilization theory, and causal factors of fossilization theory, which provided a conceptual framework for analyzing the types of consonants fossilization and the causal factor. This qualitative case study aims to examine the types of consonant fossilization and the factors that cause these errors to persist. The collected data through classroom observation along with video recording and in-depth interview were analyzed using an interactive model by Miles et al., (2014) which includes data condensation, data display, and conclusion drawing & verification. The findings reveal that there are nine fossilized English consonants, namely /z/, /v/, /θ/, /ʒ/, /t/, /p/, /g/, /d/ and /b/. Environmental, cognitive, socio-cognitive, and habitual or automatized factors have contributed to the fossilization among EFL teachers. It suggests that by increasing their awareness of English pronunciation, particularly of fossilized consonant sounds, teachers improve their teaching effectiveness. It implies the importance of strengthening pronunciation competence through targeted training and ongoing professional development in EFL contexts.